Long-term PM2.5 exposure and depressive symptoms in China: A quasi-experimental study - Tao Xue; Tianjia Guan; Yixuan Zheng; Guannan Geng; Qiang Zhang; Yao Yao; Tong Zhu (Elsevier, 2021)
Background: Air pollutants, particularly fine particulate matters (PM2.5) have been associated with mental disorder such as depression. Clean air policy (CAP, i.e., a series of emission-control actions) has been shown to reduce the public health burden of air pollutions. There were few studies on the health effects of CAP on mental health, particularly, in low-income and middle-income countries (LMICs). We investigated the association between a stringent CAP and depressive symptoms among general adults in China. Methods: We used three waves (2011, 2013 and 2015) of the China Health and Retirement Longitudinal Study (CHARLS), a prospective nationwide cohort of the middle-aged and older population in China. We assessed exposure to PM2.5 through a satellite-retrieved dataset. We implemented a difference-in-differences (DID) approach, under the quasi-experimental framework of the temporal contrast between 2011 (before the CAP) and 2015 (after the CAP), to evaluate the effect of CAP on depressive symptoms. The association was further explored using a mixed-effects model of the three waves. To increase the interpretability, the estimated impact of PM2.5 was compared to that of aging, an established risk factor for depression. Findings: Our analysis included 15,954 participants. In the DID model, we found a 10-µg/m3 reduction of PM2.5 concentration was associated with a 4.14% (95% CI: 0.41-8.00%) decrement in the depressive score. The estimate was similar to that from the mixed-effects model (3.63% [95% CI, 2.00-5.27%]). We also found improved air quality during 2011-2015 offset the negative impact from 5-years' aging. Interpretation: The findings suggest that implementing CAP may improve mental wellbeing of adults in China and other LMICs.